Studi Etnobotani Tumbuhan pada Upacara Adat Midodareni di Kabupaten Jombang - Nurmalasari, Siti; Ami, Mucharommah Sartika (Exact Papers in Compilation (EPiC), 2021)
This study aims to determine the types of plants used in the Midodareni traditional ceremony in the Jombang Regency and their philosophical meaning according to the local community. The methods used are interviews and direct observation. Interviews were conducted with three resource persons who are experts in the field of Midodareni traditional ceremonies in the Jombang Regency, with interview guide instruments. This interview was conducted to collect data on the types of plants used in these traditional ceremonies and their philosophical meanings. Direct observations were made to identify morphological characteristics and plant parts used in the traditional ceremony. The instrument used is an observation sheet. The data obtained were analyzed descriptively. The results showed that the types of plants used in the Midodareni traditional ceremony in the Jombang Regency could differ depending on the type of tumpeng used in the step procession. There are two types of tumpeng, namely tumpeng of white rice and tumpeng of pindang antep. Tumpeng white rice uses urap-urap so that more types of plants are used, compared to tumpeng pindang antep which does not use urap-urap in its components. The type of plant that must be present in the traditional ceremony is wulung sugar cane, namely black sugar cane that the bride will step over as a symbol of going to a new level of life. Overall, there are 24 types of plants used in the Midodareni traditional ceremony in the Jombang Regency.